EFFECT OF AUTOLOGOUS PLATELET-RICH PLASMA ON ARRANGEMENT OF COLLAGEN FIBERS AT INJURED ACHILLES TENDON ENTHESES IN RABBITS - Faisal, Tayyaba; Qamar, Khadija; Asjid, Rafia; Umbreen, Faiza; Sohail, Saima; Bashir, Sumyyia (Pakistan Armed Forces Medical Journal, 2019)
Objective: To evaluate the effects of autologous platelet-rich plasma on arrangement of collagen fibers at injured Achilles tendon entheses in rabbits.Study Design: Laboratory-based experimental study.Place and Duration of Study: Department of Anatomy, Army Medical College, Rawalpindi, in collaboration with National Institute of Health, Islamabad, from March to May, 2018.Material and Methods: Forty, healthy, male, “New Zealand white rabbits”, 4-6 months of age, weighing 2000- 2500g, were randomly divided into 4 equal groups (A, B, C and D). Group A served as control, while B, C and D were experimental groups. Injuries were surgically induced at Achilles tendon entheses of rabbits of experimental groups, which were treated with injections of autologous platelet-rich plasma, either at the time of inducing injury or two weeks after injury in groups C and D respectively while group B was left untreated. Animals were sacrificed after 12 weeks. Tissues were processed and stained for histological evaluation. Statistical analysis was done using SPSS version 22. A p-value of ≤0.05 was taken as significant.Results: Experimental group B showed marked deterioration in Bonar’s modified score for arrangement of collagen fibers as compared to the control group A. The scores were significantly improved in treatment groups C and D as compared to group B.Conclusions: Injection of autologous platelet-rich plasma effectively improved the Bonar modified score for arrangement of collagen fibers at injured entheses, 12 weeks after injury as compared to non-treatment group.